On Three New Techniques of Multiplication of Any Two Numbers - O. A. Safiati; Dafik Dafik; N Maylisa (Pancaran Pendidikan, 2019)
A multiplication is one of mathematical operations. It is taught in a school from elementary to high level. Most students consider the operation of multiplication is one of a complex operation. Thus, a lot of techniques are given such as the general stacking technique, the star stacking technique, the line stacking techniques, the Napier-bones technique. Those techniques have been well-known and can be found in the elementary school text book or in the internet such as google or youtube. In this paper, we develop a new technique namely a circle and square stacking technique, and a cross matching technique. Those new techniques show the advantages especially for visual learners style and gain more efficiency in terms of algorithms and number of operations needed